A imaginação e o feitiço do prático-inerte na dialética crítica sartriana - Mattos, Marcus de Dutra (2022)
The present thesis starts from the Sartrean dialectic to meet his study about image and its noematic correlative in its phenomenological phase. Our work seeks to demonstrate the possible relationship between the Sartrean phenomenological image and material inertia from the practico-inert. We seek to show the similarities and differences between the works of Jean-Paul Sartre and Karl Marx in order to propose an ontological critique of the time lived from the notion of commodity fetish and its relationship with the creation of images (of) the self in social networks. The practico-inert spell sets out to answer these questions.